Meningkatkan Motivasi dan Hasil Belajar Menggunakan Model Discovery Learning Materi Sistem Pencernaan Manusia untuk Siswa Kelas VIII-A SMP Negeri 2 Pare Kabupaten Kediri - Na, Husnaini (Jurnal Simki Pedagogia, 2023)
The purpose of this research is to test the Discovery Learning Model on the Material of the Human Digestive System. The discovery learning model was chosen because it provides opportunities for each student to actively participate in discovering concepts through concrete examples, pictures, and information from books. This research is an action research (action research), because the research was conducted to solve learning problems in the classroom. This research also includes descriptive research, because it describes how a learning technique is applied and how the desired results can be achieved. This research was conducted from September to November 2019. From this study it can be concluded that the Discovery Learning Model can increase learning motivation in the digestive system material in humans in class VIII-A students of SMP Negeri 2 Pare Kediri Regency odd semester of the 2019/2020 Academic Year of 42, 85%, where in cycle 1 it increased by 50% to 92.85% in cycle 2. The Discovery Learning model can improve learning outcomes in the digestive system material in humans for class VIII-A students of SMP Negeri 2 Pare, Kediri Regency, odd semester of the 2019/2020 Academic Year which is shown in the increase in classical completeness of 15.38% where in cycle 1 it was 74.36% increasing to 89.74% in cycle 2. The increase in classical completeness was also followed by an increase in the class average value of 7.34 from 75.76 in cycle 1 to 83.1 in cycle 2.